Reflections on judging - Posner, Richard A. (Harvard University Press, 2013)
In Reflections on Judging, Richard Posner distills the experience of his thirty-one years as a judge of the United States Court of Appeals for the Seventh Circuit. Surveying how the judiciary has changed since his 1981 appointment, he engages the issues at stake today, suggesting how lawyers should argue cases and judges decide them, how trials can be improved, and, most urgently, how to cope with the dizzying pace of technological advance that makes litigation ever more challenging to judges and lawyers.